Life Satisfaction, Occupation and Gender - Choi, Seulki; Lim, Kyungwon (Journal of Asian Sociology, 2020)
This study aims to understand the impacts of wages and occupational prestige on life satisfaction among wage workers by occupation and gender in South Korea using data from the Korea Labor and Income Panel Study (KLIPS) and analyzing it with a fixed effects ordered logit analysis. The results show that wage positively affects life satisfaction for both male and female workers but that it matters more for women. The effects are also different by occupation. Wage is more significant in the life satisfaction of male managers and clerks. Regarding prestige, it has no significant impact on the life satisfaction of male workers, but it affects female workers. By occupation, it matters more for managers, professionals, and semi-professionals but for clerks, it does not affect much among male employees. On the other hand, it dominates all occupations among female workers, so the differences in life satisfaction by occupation amongst women can be said to be mainly due to occupational prestige.